Metabolism oxalic acid: failure causes and consequences of molecular-biochemical factors for the formation of oxalate-induced diseases - Korol, L. V.; Vasylchenko, V. S. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Mechanisms mediating oxalate-induced alterations in renal have attracted the attention of scientists in recent years.Various mechanisms have been proposed to explain crystal retention. The present review assesses the biochemical mechanisms of oxalate-induced alterations and diagnostically significant markers of organ damage caused by oxalate. The article focuses on the modern data of molecular-biochemical aspects of the formation of oxalate-induced diseases.